Release of gp120 Restraints Leads to an Entry-Competent Intermediate State of the HIV-1 Envelope Glycoproteins - Alon Herschhorn (mBio, 2016)
Primary human immunodeficiency virus (HIV-1) envelope glycoprotein (Env) trimers [(gp120/gp41)3] typically exist in a metastable closed conformation (state 1). Binding the CD4 receptor triggers Env to undergo extensive conformational changes to mediate virus entry. We identified specific gp120 residues that restrain Env in state 1. Alteration of these restraining residues destabilized state 1, allowing Env to populate a functional conformation (state 2) intermediate between state 1 and the full CD4-bound state (state 3). Increased state 2 occupancy was associated with lower energy barriers between the states. State 2 was an obligate intermediate for all transitions between state 1 and state 3. State 2-enriched Envs required lower CD4 concentrations to trigger virus entry and more efficiently infected cells expressing low levels of CD4. These Envs were resistant to several broadly neutralizing antibodies and small-molecule inhibitors. Thus, state 2 is an Env conformation on the virus entry pathway; sampling state 2 increases the adaptability of HIV-1 to different host cell receptor levels and immune environments. Our results provide new insights into the conformational regulation of HIV-1 entry.